2010
DOI: 10.1042/cs20100033
|View full text |Cite
|
Sign up to set email alerts
|

Regulation in chronic obstructive pulmonary disease: the role of regulatory T-cells and Th17 cells

Abstract: COPD (chronic obstructive pulmonary disease) is an inflammatory disorder of the airways, which is associated with irreversible airway obstruction. The pathological hallmarks of COPD are destruction of the lung parenchyma (pulmonary emphysema), inflammation of the central airways (chronic bronchitis) and inflammation of the peripheral airways (respiratory bronchiolitis). Tobacco smoking is established as the main aetiological factor for COPD. A maladaptive modulation of inflammatory responses to inhalation of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 110 publications
(114 reference statements)
8
60
1
8
Order By: Relevance
“…However, there have also been some reports that are opposed to the above-mentioned results regarding the association between IL-17A and emphysema. Others have indicated that airway infiltration of CD4 + CCR6 + Th17 cells are associated with chronic cigarette smoke induced airspace enlargement [30,31] . Four-month exposure to smoke, a major stimulator of emphysema, can induce significant increases in IL-17 levels in the pulmonary airway [32] .…”
Section: Discussionmentioning
confidence: 99%
“…However, there have also been some reports that are opposed to the above-mentioned results regarding the association between IL-17A and emphysema. Others have indicated that airway infiltration of CD4 + CCR6 + Th17 cells are associated with chronic cigarette smoke induced airspace enlargement [30,31] . Four-month exposure to smoke, a major stimulator of emphysema, can induce significant increases in IL-17 levels in the pulmonary airway [32] .…”
Section: Discussionmentioning
confidence: 99%
“…К Th17 клеткам относятся CD4 + T лимфоциты, для которых характерна секреция IL 17A, IL 17F и IL 22 [71,72]. Кроме того, IL 17 синтезируется естествен ными киллерами, цитотоксическими Т лимфоцита ми и гранулоцитами.…”
Section: ингибиторы популяции Th17 клетокunclassified
“…Кроме того, IL 17 синтезируется естествен ными киллерами, цитотоксическими Т лимфоцита ми и гранулоцитами. IL 17 опосредованно способ ствует привлечению нейтрофилов и лимфоцитов из крови в очаг воспаления в легких путем стимуляции секреции провоспалительных хемокинов IL 8, CCL20 и CXCL10 эпителиальными клетками возду хоносных путей и альвеолярными макрофагами [71,73,74]. Кроме того, этот цитокин стимулирует обра зование MMP 9 в клетках эпителия дыхательных пу тей [75].…”
Section: ингибиторы популяции Th17 клетокunclassified
See 1 more Smart Citation
“…A deficiency of Tregs can impair the immune system tolerance for autoantigens and lead to autoimmune disease [15]. The behaviour of Tregs in COPD is of interest and seems to vary with the site in the lung and severity of the population studied [16]. Long-term smoking exposure, but not the development of airflow obstruction, increases Treg numbers in the lung [17].…”
Section: How Could the Inflammation Be Suppressed?mentioning
confidence: 99%